PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMA NEGERI 3 RAMBAH HILIR - Yeni, Elvita; -, Hardianto; -, Suwandi (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
This study examines the effect of cooperative learning model Jigsaw on the results of students mathematics learning. Thepopulation in this study class X SMA Negeri 3 Rambah Hilir. The sampling technique is done by sampling jenuh. Samples X2 class as the experimental class and the class as a class X1 control. With the test of normality and homogeneity tests showed the two samples are normally distributed and not homogeneous. Analysis of the data using the â² Because â² Â Â  = H0 is rejected. So it is concluded that there are significant Jigsaw cooperative learning model for students mathematicslearning outcomes.